2016
DOI: 10.1002/1873-3468.12129
|View full text |Cite
|
Sign up to set email alerts
|

Temperature homeostasis in mice lacking the p43 mitochondrial T3 receptor

Abstract: Thyroid hormones and Thra gene play a key role in energy expenditure regulation, temperature homeostasis, and mitochondrial function. To decipher the function of the mitochondrial TRa receptor in these phenomena, we used mice lacking specifically the p43 mitochondrial T3 receptor. We found that these animals were hypermetabolic, hyperphagic, and displayed a down setting of the core body temperature. However, p43À/À animals do not present cold intolerance or defect of facultative thermogenesis. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The overproduction of TH increases energy demand and mitochondrial activity, and as a consequence of the latter, there is an increase in the production of ROS [27]. Several authors have described the presence of T3 receptors in mitochondria [9, 28], whereby the TH could also exert direct actions on mitochondrial activity that contribute to the increase in ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of TH increases energy demand and mitochondrial activity, and as a consequence of the latter, there is an increase in the production of ROS [27]. Several authors have described the presence of T3 receptors in mitochondria [9, 28], whereby the TH could also exert direct actions on mitochondrial activity that contribute to the increase in ROS.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, variation in TH receptor expression (either nuclear or mitochondrial) has not been studied in response to temperature variation in birds. In mice and rats, mitochondrial receptor p43overexpression was recently found to be associated with higher Tb (Bertrand-Gaday et al, 2016). In vivo (knockout) and in vitro studies in mice revealed that p43 is associated with mitochondrial biogenesis, activity, mito-nuclear crosstalk and even muscle metabolic and contractive phenotype (reviewed in Wrutniak-Cabello et al, 2017;Wrutniak-Cabello et al, 2018), but similar data is lacking from birds.…”
Section: Endocrine and Molecular Mechanisms Of Thermoregulation In Birdsmentioning
confidence: 99%
“…The SC2 and SC7 (n = 87 + 141) displayed highest activity at D0 and then decreased thereafter, suggesting TFs within these clusters are likely involved in maintaining the thermogenic phenotype of BAT. The TFs in SC2 and SC7 overlapped with many known key thermogenic TFs, such as the EBF1 (Angueira et al, 2020), EBF2 (Stine et al, 2016), NFIA (Hiraike et al, 2017), RORA (Auclair et al, 2021), ESSRG (Müller et al, 2020) and THRA (Bertrand-Gaday et al, 2016), explaining their activity at the beginning of thermogenic adaptation in the extrauterine low-temperature environment. As an example, the aggregated decreased footprint signals of EBF2 on the genome were shown in Supplementary Figure S3B.…”
Section: Genome-wide Footprinting Analysis Revealed Sequential Regula...mentioning
confidence: 97%